Educational Policy Reforms in Zimbabwe Since 1980: Foundations for a Transformative Higher Education Curriculum - Young Mudavanhu; Pinias Chikuvadze; Claretah Makuvire; Daimond Dziva (Quality Assurance Practices for Transformative Higher Education in Southern Africa, 2025)
This chapter examines how the conservative reforms of the transitional government (1978-1980), particularly the Education Act of 1979, reinforced colonial-era inequalities. In a move targeted at addressing this imbalance soon after independence, the government embarked on more radical reforms in education. For instance, the Education Act 1987 was targeted at intensifying the provision of education, including the removal of discriminatory practices that were put in place by the colonial government. In the 1990s, the Zimbabwean government reviewed its educational goals guided by the Education Act 1987 (as amended in 1996) to support efficient and quality education. This called for the adoption of programmes of continuing professional development premised on the drive to move education from an academic approach to a competency-based approach. Thus, the Education Act 1987 (as amended in 2006) implemented a ’two-path way’ education structure based on the belief that all students leave school with at least one subject from the skills area path. Based on the 1999 Presidential Commission of Inquiry in Education and Training, a framework for primary and secondary education (2015 - 2022; 2024 - 2030) was introduced with an emphasis outcome-based approach to learning. It is imperative to conclude that the colonial regulatory framework and statutory provisions created the glaring inequalities, which have been addressed upon the attainment of independence through various phases geared towards creating a foundation for a transformed higher education guided by the ethos of quality assurance.